EXPLORING CHALLENGES FACED BY MALAYSIAN EXPAT-PRENEURS IN INTERNATIONAL ENTREPRENEURSHIP SECTOR AND STRATEGIES TO OVERCOME. A QUALITATIVE STUDY ON SELF-INITIATED EXPATRIATES - Yusuf, Bibi Noraini (Advances in Social Sciences Research Journal, 2020)
Numerous terms have been associated with expat-preneurs, such as expatriates and Self-Initiated Expatriates (SIEs), in order to explore more about the exact terminology and other attributes. How do expat-preneurs brace themselves in adapting to their new environment, meet varied challenges, overcome an array of obstacles, and solving problems? This research study is to uncover the reality checks of typical expat-preneurs, exposing to the world what it takes to become an expat-preneur. The main objective of this research is to explore the truth about an expat-preneur’s lifestyles, specifically focusing on two main themes, Malaysian citizens that have become expat-preneurs and those opening their own business abroad. This study will focus on three main topics, these being factors affecting Malaysians to become expat-preneurs, obstacles that they faced when opening their business abroad, and lastly how they managed to overcome these obstacles. Five (5) Malaysian citizens staying and living abroad were selected as respondents to participate in the interview sessions and the selection was conducted by using a snowball sampling methodology. The respondents came from five (5) different countries, namely Qatar, Egypt, Singapore, Indonesia, and Thailand. At the conclusion of the research study, the results show that the reasons why these Malaysian citizens became expat-preneurs were mainly due to (1) accompanying their spouses on overseas assignment, and (2) opportunity to earn side income while abroad. The obstacles most commonly faced when opening a business abroad were (1) financial problems, (2) marketing obstacles, and (3) no basic knowledge of business and management. Finally, the strategies to overcome these obstacles were (1) taking bank loans or borrowing money from family members and (2) acquire knowledge about business and marketing from friends. These findings are useful and shall serve as basic guidelines to Malaysians who want to be expat-preneurs in the near future. It helps Malaysian expat-preneurs to comprehend an array of hardships before starting a business abroad.